Understanding Muzakki Loyalty in Eastern Indonesia: The Role of Sharia Governance, Religiosity, and Satisfaction - Susanto, Mei; Pujiyanto, Eko; Damayanti, Retno Wulan (Media Ekonomi dan Manajemen, 2026)
This study investigates the determinants of Muzakki loyalty by developing an integrated model that incorporates sharia governance, trust, religiosity, satisfaction, and willingness to pay more. The research focuses on Muzakki who pay zakat through the National Zakat Board (Baznas) in Central Maluku Regency, Ambon City, and Buru Regency. Using a quantitative approach, the study employs Partial Least Squares-Structural Equation Modeling (PLS-SEM) to analyze data obtained from 172 respondents selected through purposive sampling. The findings reveal that sharia governance strengthens Muzakki trust, religiosity enhances satisfaction, and satisfaction plays a central role in driving loyalty. The results suggest that improving transparency, accountability, and sharia compliance can reinforce trust and overall satisfaction. Enhancing service quality and nurturing religious commitment are equally important to cultivate stronger loyalty. This study highlights the strategic importance of robust sharia governance and service excellence in sustaining long-term Muzakki engagement in zakat management across Maluku Province.